Effects of immunosuppressive drugs on COVID‐19 severity in patients with autoimmune hepatitis. (13th December 2021) - Efe, Cumali; Lammert, Craig; Taşçılar, Koray; Dhanasekaran, Renumathy; Ebik, Berat; Higuera‐de la Tijera, Fatima; Calışkan, Ali R.; Peralta, Mirta; Gerussi, Alessio; Massoumi, Hatef; Catana, Andreea M.; Purnak, Tugrul; et al.
Abstract: Background: We investigated associations between baseline use of immunosuppressive drugs and severity of Coronavirus Disease 2019 (COVID‐19) in autoimmune hepatitis (AIH). Patients and methods: Data of AIH patients with laboratory confirmed COVID‐19 were retrospectively collected from 15 countries. The outcomes of AIH patients who were on immunosuppression at the time of COVID‐19 were compared to patients who were not on AIH medication. The clinical courses of COVID‐19 were classified as (i)‐no hospitalization, (ii)‐hospitalization without oxygen supplementation, (iii)‐hospitalization with oxygen supplementation by nasal cannula or mask, (iv)‐intensive care unit (ICU) admission with non‐invasive mechanical ventilation, (v)‐ICU admission with invasive mechanical ventilation or (vi)‐death and analysed using ordinal logistic regression. Results: We included 254 AIH patients (79.5%, female) with a median age of 50 (range, 17‐85) years. At the onset of COVID‐19, 234 patients (92.1%) were on treatment with glucocorticoids (n = 156), thiopurines (n = 151), mycophenolate mofetil (n = 22) or tacrolimus (n = 16), alone or in combinations. Overall, 94 (37%) patients were hospitalized and 18 (7.1%) patients died. Use of systemic glucocorticoids (adjusted odds ratio [aOR] 4.73, 95% CI 1.12‐25.89) and thiopurines (aOR 4.78, 95% CI 1.33‐23.50) for AIH was associated with worse COVID‐19 severity, after adjusting for age‐sex, comorbidities and presence of cirrhosis. Baseline treatment with mycophenolate mofetil (aOR 3.56, 95% CI 0.76‐20.56) and tacrolimus (aOR 4.09, 95% CI 0.69‐27.00) were also associated with more severe COVID‐19 courses in a smaller subset of treated patients. Conclusion: Baseline treatment with systemic glucocorticoids or thiopurines prior to the onset of COVID‐19 was significantly associated with COVID‐19 severity in patients with AIH.